Algorithm Trading using Python in Financial Markets - Fernandes, Treyhan; Guptia, Rahul (Journal of Advanced Research in Applied Artificial Intelligence and Neural Network; Vol 5 No 2 (2021): Journal of Advanced Research in Applied Artificial Intelligence and Neural Network, 2022)
Algorithmic trading is defined as using computer-generated algorithms to create and execute market orders. More recently, such logos trading strategies have been increasingly associated with a negative impact on major markets-both from a technical and business perspective. However, there are positive effects on algorithmic trading and-such as inflation and the elimination of market inefficiencies-far outweigh the potential negative consequences. Apart from this, algo trading has become increasingly popular and accepted in many of the world’s major markets, requiring well-thought-out strategies that help traders and investors make more than just the right return on their investment. How to cite this article: Fernandes T, Guptia R. Algorithm Trading using Python in Financial Markets. J Adv Res Appl Arti Intel Neural Netw 2021; 5(2): 1-4.